Bacteria and archaea involved in anaerobic mercury methylation and methane oxidation in anaerobic sulfate–rich reactors. (July 2021) - Du, Hongxia; Sun, Tao; Liu, Yang; An, Siwei; Xie, Haiying; Wang, Dingyong; Igarashi, Yasuo; Imanaka, Tadayuki; Luo, Feng; Ma, Ming
Abstract: The identification of dominant microbes in anaerobic mercury (Hg) methylation, methylmercury (MeHg) demethylation, and methane oxidation as sulfate-reducing bacteria, methanogens or, probably, anaerobic methanotrophic archaea (ANMEs) is of great interest. To date, however, the interrelationship of bacteria and archaea involved in these processes remains unclear. Here, we demonstrated the dynamics of microorganisms participating in these processes. Anaerobic fixed-bed reactors were operated with swine manure and sludge to produce methane stably, and then, sulfate (reactor C), sulfate and Hg(II) (reactor H), and sulfate and MeHg (reactor M) were added, and the reactors were operated for 120 d, divided equally into four periods, P1–P4. The bacterial compositions changed nonsignificantly, whereas Methanosaeta in reactors H and M decreased significantly, revealing that it was irrelevant for Hg transformation. The abundances of Syntrophomonadaceae, Methanoculleus, Candidatus Methanogranum and Candidatus Methanoplasma increased continuously with time; these species probably functioned in these processes, but further evidence is needed. Desulfocella and Desulfobacterium dominated first but eventually almost vanished, while the dominant archaeal genera Methanogenium, Methanoculleus and Methanocorpusculum were closely related to ANME–1 and ANME–2. PLS-DA results indicated that both bacteria and archaea in different periods in the three reactors were clustered separately, implying that the microbial compositions in the same periods were similar and changed markedly with time. Graphical abstract: Image 1 Highlights: Methanosaeta decreased significantly after adding Hg and was unrelated to Hg transformation. Desulfocella and Desulfobacterium dominated first but finally almost vanished. The dominant archaeal genera were closely related to ANME–1 and ANME–2. Microbes in different periods clustered separately, showing a significant change with time.